Nordhaus-Gaddum Type Relations on Open Support Independence Number of Some Path Related Graphs Under Addition and Multiplication (Baghdad Science Journal, 2023)
In this paper, Nordhaus-Gaddum type relations on open support independence number of some derived graphs of path related graphs under addition and multiplication are studied.